Cost-effectiveness analysis of first-line treatment for chronic hepatitis B in China. (February 2022) - Dai, Zonglin; Wong, Irene O.L.; Xie, Chan; Xu, Wenxiong; Xiang, Yu; Peng, Liang; Lau, Eric H.Y.
Abstract: Objectives: Hepatitis B virus infection is an important public health problem. We analysed the cost-effectiveness of the first-line therapies, including nucleotide analogues (namely tenofovir alafenamide fumarate (TAF), tenofovir disoproxil fumarate (TDF) and entecavir) and pegylated interferon (Peg-IFN) for patients with chronic hepatitis B (CHB) in China. Methods: A Markov model describing CHB disease progression was constructed to compare the cost-effectiveness of the first-line therapies, considering both satisfactory (HBeAg seroconversion) and optimal (HBsAg seroclearance) treatment goals. We examined the main outcomes, including cumulative lifetime cost per patient, incremental quality-adjusted life years (QALYs), incremental cost-effectiveness ratio and net monetary benefit. Uncertainty analysis was conducted to identify key influential parameters. Results: Compared with the baseline strategy, Peg-IFN had the highest QALY gain for HBeAg-positive (HBeAg+) CHB patients achieving a satisfactory goal and an optimal goal (3.19 and 6.32 respectively), and TDF was the most cost-effective therapy for HBeAg-negative CHB patients (1418/QALY) achieving a satisfactory goal. Among nucleotide analogues, TAF was the most-effective strategy and had higher acceptability to achieve an optimal goal in the Eastern region of China (under 1 x GDP per capita threshold). Conclusions: Among nucleotide analogues, TDF was the most cost-effective treatment in China for CHB patients to achieve satisfactory and optimal treatment goals, whereas TAF was cost-effective and more effective in the wealthier region. Peg-IFN was most cost-effective among HBeAg+ CHB patients to achieve both goals, with better clinical outcomes. Our findings also indicate the importance of regular monitoring during and after CHB treatment, and could inform treatment strategies in China and other countries.